Theology and Myth in James McAuley's Captain Quiros - Rowe, Noel (Pacifica, 1991)
This article considers the reciprocal relationship between the theological concerns and the imaginative intentions which characterise James McAuley's long narrative poem Captain Quiros. Giving particular attention to the tensions established between hope and despair, between eschatology and history, the article argues that the poem's religious imagination is most profoundly informed, not by its theology of Providence, but by its sympathy for the myth of the Fall.